Study of Some Physical and Antibacterial Properties of Bio-based (PLA)/(PCL) Blend reinforced with ZrO2 Nanoparticles - Ashoor, Hassan A.; Mohammed, Awattif A. (Iraqi Journal of Physics, 2024)
The aim of this study was to produce flexible films by combining polylactic acid (PLA) and poly(ε-caprolactone) (PCL), and enhance their strength by reinforcing them with different weight percentages (0.75, 1.5, and 2.25%) of zirconium oxide (ZrO2) nanoparticles (NPs) using a solvent casting process. The physical and antibacterial properties of the films were analysed to determine their suitability for use in food packaging. X-ray diffraction (XRD) patterns of the PLA/PCL films containing 2.25% by weight ZrO2 nanoparticles have a peak at an angle of 2θ = 17.18°, accompanied by smaller peaks. This confirms that these thin films have a semi-crystalline structure and that the molecules in the thin films are well dispersed. Scanning electron microscopy (SEM) analysis of the film surfaces reveals that the pure PLA/PCL films exhibit a smooth surface, while the (PLA/PCL/ZrO2NPs) films have a rough surface. The thermal behaviour of the blends through differential scanning calorimetry (DSC) showed fluctuations due to variations in the reinforcement ratio, resulting in changes in the glass transition and melting temperatures. These oscillations indicate changes in the level of crystallinity. ZnO2 has antibacterial properties that promote growth inhibition, making these films more effective in food packaging.